The Association Between Maternal Age, Hemoglobin Levels, and Parity with the Incidence of Low Birth Weight (LBW) at RSUD Dr. Pirngadi Medan, 2022–2023 - Indriani Afrilita Saragih; Elizabeth Septianur Girsang; Alexander Parlindungan Marpaung; Suryati Sinurat; Harry Butarbutar (Jurnal Kedokteran Methodist, 2025)
Background: Low Birth Weight (LBW) can be defined as a baby weighingless than 2500 grams or 5.5 pounds. The causes of LBW are generallymultifactorial, including maternal factors, pregnancy factors, fetal factors,and other factors. Based on research that has been conducted, severalmaternal factors that can influence the occurrence of LBW include age,hemoglobin levels, and maternal parity.Research Objectives: The purpose of this study is to analyze therelationship between maternal age, hemoglobin levels and parity and theincidence of LBW babies in mother giving birth at Dr. pirngadi Hospital in2022-2023.Methods: This study used an observational-analytic method with a cross-sectional research design.Research Result : The total number of research samples is 119 samples.The analysis used chi square test at p < 0,05. The result showed that agehave a correlation with the incidence of LBW with a p-value 0,036(<0,05), maternal hemoglobin levels also have a correlation with theincidence of LBW with p-value 0,022(0,05) and parity has correlation withthe incidence of LBW with p-value 0,031(<0,05).Conclusion :Maternal age, hemoglobin levels and parity are associatedwith the incidence of LBW at Dr. Pirngadi Hospital in 2022-2023.Keywords : LBW, Age, Maternal Hemoglobin levels, Parity